2019
DOI: 10.1161/atvbaha.119.312509
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Triggers Osteochondrogenic Differentiation of Vascular Smooth Muscle Cells in an HIF-1 (Hypoxia-Inducible Factor 1)–Dependent and Reactive Oxygen Species–Dependent Manner

Abstract: Objective— Vascular calcification is associated with high risk of cardiovascular events and mortality. Osteochondrogenic differentiation of vascular smooth muscle cells (VSMCs) is the major cellular mechanism underlying vascular calcification. Because tissue hypoxia is a common denominator in vascular calcification, we investigated whether hypoxia per se triggers osteochondrogenic differentiation of VSMCs. Approach and Results— We studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 73 publications
3
87
0
3
Order By: Relevance
“…Growing evidence suggests that hypoxia and HIFs play a vital role in vascular calcification, and targeting HIF blocks mineralization in hypoxia (Mokas et al, 2016;Balogh et al, 2019). Our results presented here support the link between HIFs and vascular calcification.…”
Section: Discussionsupporting
confidence: 86%
“…Growing evidence suggests that hypoxia and HIFs play a vital role in vascular calcification, and targeting HIF blocks mineralization in hypoxia (Mokas et al, 2016;Balogh et al, 2019). Our results presented here support the link between HIFs and vascular calcification.…”
Section: Discussionsupporting
confidence: 86%
“…Hypoxia-inducible factor 1α (HIF-1α), a transcription factor upregulated by hypoxia, can drive aerobic glycolysis. In addition to previous literature suggesting a critical role of HIF-1α in Pi-induced VC [293], another recent study demonstrated that hypoxia-dependent HIF-1α upregulates Runx2, thereby inducing calcification of mouse aorta [294]. These findings indirectly suggest a role of mitochondrial dysfunction in VC, given that HIF-1α is also upregulated in mitochondrial dysfunction.…”
Section: Mitochondrial Dysfunction and Defective Mitophagy In Vascumentioning
confidence: 57%
“…They also showed that the variety in cell density in the different regions of gradient scaffolds could be attributed to the increase of hypoxia inducible factor (HIF) in the higher hypoxic regions of small pore size where the oxygen levels could drop [35]. Previous studies already suggested that rising hypoxia leads to osteochondrogenic differentiation, mediated via HIF-1 and triggered through the elevation of ALP and OCN levels and mineralization [36][37][38][39]. Interestingly, we also found more calcium mineralization in smaller pore sizes of 250 μm and offset.50.50 structures.…”
Section: Discussionmentioning
confidence: 99%